The impact of anatomical recipient liver abnormalities on rat liver transplantation - Chen, Yongfeng; Li, Wenzhong; Chen, Guoyong; Zhou, Shaotang (Frontiers in Veterinary Science, 2025)
BackgroundOrthotopic rat liver transplantation (OLT) is widely used in basic research; normal liver anatomy and structures are attributable to its success, but its deformities are complicated by a negative OLT.MethodsFor tolerance induction, we used OLT from Lewis to Brown Norway (BN) rats as a chronic rejection model and encountered two anatomical deformities in the recipient livers. The outcomes of OLT were analyzed.ResultsOf the 47 liver transplantations, the accessory liver lobe occurred in four cases, and bifurcations of liver outflow occurred in five cases in BN rats. For the accessory liver lobe, we discontinued OLT in one patient with a large accessory liver lobe. Two rats died from pneumothorax upon separation, and one case succeeded with a small lobe. For two vein outflow orifices of the liver, we succeeded in OLT due to its reconstruction in one case; however, the recipient died 1 week later in one case, after one small orifice was sutured. We failed in three cases due to thrombosis following OLT. Among the 38 rats with normal liver anatomy, only four failed to survive the LT. There were significant differences in OLT success (p < 0.01).ConclusionThe recipient’s liver abnormal anatomical structure has a negative impact on OLT, suggesting that pretransplant comprehensive screening is important and that clinicians are cautious in clinical practice.